Integrated transcriptome and proteome analyses reveal candidate genes for ginsenoside biosynthesis in Panax japonicus C. A. Meyer - Huang, Chaokang; Li, Pengfei; Yang, Xiaolin; Niu, Tengfei; Zhao, Shujuan; Yang, Li; Wang, Rufeng; Wang, Zhengtao (Frontiers in Plant Science, 2023)
Panax japonicus C. A. Meyer is a plant of the Araliaceae family, and its rhizomes can be used as dietary supplements. It is extremely rich in bioactive components ginsenosides with benefits to human health. However, the underlying mechanisms of ginsenosides biosynthesis in Panax japonicus remains poorly understood. Therefore, a comprehensive analysis of the metabolites, transcriptome, and proteome was conducted to investigate ginsenoside metabolism of Panax japonicus. Here, three types of ginsenosides were found to exhibited tissue-specific distribution using the liquid chromatography–mass spectrometry method. Next, differentially expressed gene analysis revealed that transcript levels of ginsenosides biosynthetic genes have significant differences between differential samples. In addition, correlation analysis showed that the ginsenosides content was closely related to the expression level of 29 cytochrome P450s and 92 Uridine diphosphate-glycosyltransferases. Finally, phylogenetic analysis was performed for the target proteins to conduct preliminary studies on their functions and classification. This study provides insight into the dynamic changes and biosynthetic pathway of ginsenosides and offers valuable information on the metabolic regulation of Panax japonicus.